Laboratory study investigating the impact of different LCMs additives on drilling mud rheology and filtration - Aleqabi, Zainab Jawad; A. Alrazzaq, Ayad A. Alhaleem; Kwesi Wayo, Dennis Delali (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Drilling operations in Basra’s oil fields, particularly targeting the Dammam, Hartha, and Shuaiba formations, are facing significant challenges related to lost circulation. This study investigates the effects of incorporating lost circulation materials (LCMs) into bentonite-based and polymer-based drilling muds. Experiments were carried out using a high-pressure high-temperature filter press to evaluate the rheological properties and filtration performance of the different mud systems prepared using bentonite and polymer mixed with various compositions of additives. The results showed that the incorporation of LCMs increased the plastic viscosity and yield point of the polymer mud by 25-30%, while the impact on the bentonite mud was less significant. Notably, the using of fine-sized LCMs influenced the rheological characteristics of the polymer mud system, resulting in a 35-40% increase in parameters as the LCM concentration was raised. In terms of filtration performance, the bentonite mud exhibited the highest total fluid loss, whereas the polymer mud showed the lowest. The adding of LCMs led to a 20-25% reduction in fluid loss for both mud systems, with fine-sized LCMs at higher concentrations proving most effective in the polymer mud. In conclusion, this study demonstrates the substantial influence that the type, size, and concentration of LCMs can have on the rheological and filtration properties of drilling muds. It is confirmed that the polymer mud system is particularly sensitive to these LCM parameters. Desalination elimination of 80.95% associated with a maximum power output of 420 mW/m3 in the system.